Strengthening the digital community space and English village initiative for sustainable smart village development in Bumi Harjo - Almustari A. Enteding; Nadya Septiani Rahman; Muhlin; Yuliana Mangendre; Nurlaela (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2026)
This community service program aimed to empowering the Village Digital Community Space (RKDD) and developing Digital-English Villages. Conducted in Bumi Harjo Village, Moilong District, Banggai Regency, Central Sulawesi, over an eight-month period, this program addressed the issue of local RKDD which has not been running optimally. As it tends to limit its function as an administrative facilitator with the absence of sustainable digital literacy improvement activities. The implementation method uses the Participatory Action Research (PAR) approach by involving the village government, 10 RKDD managers as the primary target, academics from Tompotika Luwuk University, and the local community. Evaluation was conducted through pre-and post-activity competency assessments and satisfaction surveys. Activities include socialization, preparation of roadmaps, training, mentoring, and development of the "English Go" Android and desktop application, and official website Kampung Inggris Digital Bumi Harjo (Bumi Harjo Digital-English Village). The results of the program show a significant increase in the RKDD empowerment level, rising from 40 percent to 92 percent, indicating the strengthening of the function of RKDD as a digital literacy center. The implementation of the Digital-English Village reached a 90 percent completion rate, providing innovations in the form of applications and websites. The existence of the Digital-English Village strengthens village identity and opens up technology-based economic opportunities.